How fighting ends a history of surrender - Afflerbach, Holger; Strachan, Hew. (Oxford : Oxford University Press, 2012)
The history of surrender is one of the most neglected in the history of war, and yet it is vital to understanding not only how wars end but also how they are contained. This is a book with a chronological sweep that runs from the Stone Age to the present day, written by a team of truly distinguished scholars.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Capitulations, Military -- History; War -- History